2017 Survey of National Development Banks - World Bank Group (World Bank, Washington, DC, 2018)
This paper presents the main findings of the 2017 survey on national development banks that the World Bank conducted in collaboration with the World Federation of Development Financing Institutions. Sixty-four development banks from different parts of the world, mainly from middle-income countries, participated in the survey.